Assessment of anxiety levels and marital relationships among women undergoing infertility treatment: A descriptive observational study - Naima M. Elsayed; Nabila S. Mohamed; Rabab S. Hassan; Eshrak S. Hashem; Randa M. Abobaker (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This study aimed to assess anxiety levels and marital relationships among women undergoing infertility treatment. A descriptive observational design was conducted involving 300 infertile women over nine months at Zagazig University Hospital. Data were collected using a Structured Interview Questionnaire, the Female Sexual Function Index (FSFI), and the Taylor Anxiety Scale. Reliability analysis showed high internal consistency (Cronbach's alpha: 0.923 for FSFI; 0.845 for Taylor Scale). Results indicated that 32.6% of participants sought services after one year of marriage, 30.5% visited more than five centers, and 47.5% used IVF. Nearly half of the subjects experienced varying degrees of anxiety (moderate to very severe), which significantly impacted sexual arousal, orgasm, and satisfaction. In conclusion, anxiety and psychosexual dysfunction are highly prevalent among women during fertility treatments, underscoring the critical need to integrate psychological counseling and standardized screening protocols within routine reproductive healthcare.